Pola Konten Pemberitaan Pemilu 2024 dan Ideologi Moderatisme di Media Keislaman Online - Romadlan, Said (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2024)
This study aims to comprehend the pattern of news content of Indonesia's 2024 presidential election and the ideology on the media suaramuhammadiyah.id and NU online during the presidential election campaign. Using a qualitative content analysis method, this study found that the news content of the two online Islamic media had different patterns in issue selection and source determination. Meanwhile, in the category of content tendencies, the two online media showed relatively the same pattern, that is, both were neutral. This study also found that the news content of the media suaramuhammadiyah.id and NU online was influenced by the ideology of moderation. This can be seen from the tendency of the content of the two online media which disseminated moderate Islamic ideology developed by Muhammadiyah and NU. The tendency of neutrality is in accordance with the values of Muhammadiyah and NU moderation, as contained in the doctrine of Muhammadiyah's